Efficacy and Safety of Tranexamic Acid in Preventing Rebleeding after Subarachnoid Hemorrhage: A Randomized Controlled Trial (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Recent studies have indicated that early, short-course therapy with Tranexamic Acid (TXA) along with standard treatment for prevention of ischemia in aneurysmal Subarachnoid Hemorrhage (SAH) may be beneficial in preventing rebleeding and improving outcome. The study aimed to assess the efficacy and safety of short-course early administration of TXA combined with standard treatment to prevent rebleeding after SAH.Materials and methods: Seventy-four patients suffering from SAH verified on Computed Tomography (CT) scan within 72 hours after the primary hemorrhage were randomized into two treatment arms [37 received TXA and standard treatment (Experimental group), 37 received standard treatments only (Control group)]. TXA 1 gm was given intravenously slowly over 10 minutes, followed by 1 gm iv eight hourly up to a maximum of 72 hours. They were followed up for one month to observe rebleeding and outcome by Glasgow Outcome Scale.Results: Effective sample size was 70 (35 in TXA, 35 in the no-TXA group) due to the dropout of 4 patients. Out of 70 patients, 21 (30%) had rebleeding, and most of the rebleeding (95.23%) occurred after 72 hours of the initial event. Patients who had rebleeding had comparably lower GCS scores at presentation. Out of 21 rebleeding cases, 20 (95.23%) died within one month from the symptom onset. There was no significant difference (p=0.434) in rebleeding rate in TXA-treated patients (25.7%) versus non-TXA patients (34.3%). Treatment with TXA had no beneficial effect on one-month outcome (p>0.05).The adverse events were similar in the two groups and none of the patients had a seizure.Conclusions: Early short course TXA was tolerable as add-on to standard treatment of SAH but had no significant beneficial effect in reducing rebleeding and in improving one-month outcome.Chatt Maa Shi Hosp Med Coll J; Vol.21 (2); July 2022; Page 25-29